PENGEMBANGAN SISTEM COMPUTER BASED TEST (CBT) TINGKAT SEKOLAH - Sugiyono Sugiyono; Sutarman Sutarman; Tri Rochmadi (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2019)
Evaluation activities are part of the learning process at every level of education. The evaluation model or method also varies, from written tests to practical tests. Of the many evaluation methods, written evaluation or written test is an evaluation method that takes up a lot of paper, which is about 166 million pieces of paper for one national examination throughout Indonesia. The purpose of this study is to use a Computer Based Test (CBT) system that can be used as an alternative to overcome the problem of excessive paper use. The research method used in this study is R & D combined with ADDIE learning design concepts. This CBT system uses the PHP (Persolan Hypertext Preprocessor) programming language with a MySQL database connection to manage the content of the CBT system itself. This CBT system is intended for junior high / high school / vocational / equivalent levels with a trial percentage value of 83.34% for product validation test, 100% for operator user test and 88.94% for user test.